Who moves whom during primitive streak formation in the chick embryo - Chuai, Manli (HFSP Publishing, 2009)
Gastrulation is a critical stage in the development of all vertebrates. During gastrulation mesendoderm cells move inside the embryo to form the gut, muscles, and skeleton. In amniotes the mesendoderm cells move inside the embryo through a structure known as the primitive streak, extending from the posterior pole anterior through the midline of the embryo. Primitive streak formation involves large scale cell flows of a layer of highly polarized epithelial epiblast cells. The epiblast is separated from a lower layer of hypoblast cells through a well developed basal lamina. Recent experiments in which in vivo extracellular matrix dynamics was followed via labeling with fibronectin specific fluorescent antibodies and time-lapse microscopy have suggested that extracellular matrix dynamics essentially coincides with the observed epiblast cell displacements (Zamir et al., 2008, PLoS Biol 6, e247). These observations raise the important question of who moves whom and where do cells derive traction. We discuss these matters and their implications for our understanding of the mechanisms underlying cell flows during primitive streak formation in the chick embryo.